SARS-CoV-2 induced abducens nerve palsy: A case report and response to methylprednisolone - João Hugo Abdalla Santos; Ligia Fernandes Abdalla; Cleitiene de Souza Sierpinski; Camila Feldberg Porto; Felipe Gomes Naveca (IDCases)
Introduction: The abducens nerve (sixth cranial nerve) is a motor nerve that innervates the lateral rectus muscle, playing a key role in ocular abduction. Palsy of this nerve leads to convergent strabismus and diplopia. Common causes include strokes, trauma, inflammation, and infections, though in some cases, the etiology remains undetermined. With the emergence of COVID-19, neurological manifestations such as cranial neuropathies, including abducens nerve palsy, have been reported. Case presentation: We present a case of a previously healthy 48-year-old male diagnosed with SARS-CoV-2 infection who developed abducens nerve palsy in the left eye. Following the resolution of respiratory symptoms, strabismus persisted. Treatment with methylprednisolone was initiated, resulting in partial recovery within one week and complete resolution after three months. Conclusion: SARS-CoV-2-induced abducens nerve palsy can be reversible with conservative treatment using methylprednisolone. Early recognition and appropriate management are crucial for achieving a favorable prognosis.